Unravelling the genome of long chain N-acylhomoserine lactone-producing Acinetobacter sp. strain GG2 and identification of its quorum sensing synthase gene - How, Kah Yan; Hong, Kar-Wai; Sam, Choon-Kook; Koh, Chong-Lek; Yin, Wai-Fong; Chan, Kok-Gan (Frontiers in Microbiology, 2015)
Myriad proteobacteria use N-acyl homoserine lactone (AHL) molecules as quorum-sensing (QS) signals to regulate different physiological functions, including virulence, antibiotic production and biofilm formation. Many of these proteobacteria possess LuxI/LuxR system as the QS mechanism. Recently, we reported the 3.89 Mb genome of Acinetobacter sp. strain GG2. In this work, the genome of this long chain AHL-producing bacterium was unravelled which led to the molecular characterization of luxI homlogue, designated as aciI. This 552 bp gene was cloned and overexpressed in Escherichia coli BL21(DE3). The purified protein was approximately 20.5 kDa and is highly similar to several autoinducer proteins of LuxI family among Acinetobacter species. To verify the AHL synthesis activity of this protein, high resolution liquid chromatography-mass spectrometry analysis revealed the production of 3-oxo-dodecanoyl homoserine lactone and 3-hydroxy dodecanoyl homoserine lactone from induced E.coli harboring the recombinant AciI. Our data show for the first time, the cloning and characterization of the luxI homologue from Acinetobacter sp. strain GG2, and confirmation of its AHLs production. These data are of great significance as the annotated genome of strain GG2 has provided a valuable insight in the study of autoinducer molecules and its roles in QS mechanism of the bacterium.